2014
DOI: 10.1371/journal.pone.0098429
|View full text |Cite
|
Sign up to set email alerts
|

Separation from the Dam Causes Negative Judgement Bias in Dairy Calves

Abstract: Negative emotional states in humans are associated with a negative (pessimistic) response bias towards ambiguous cues in judgement tasks. Every mammalian young is eventually weaned; this period of increasing nutritional and social independence from the dam is associated with a pronounced behavioural response, especially when weaning is abrupt as commonly occurs in farm animals. The aim of the current study was to test the effect of separation from the cow on the responses of dairy calves in a judgement task. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 30 publications
4
71
1
2
Order By: Relevance
“…After separation, however, this approach response dropped to 62%, even though they continued to perform well with true white or red stimuli. The results suggested that, much like humans, when cows are distressed, they exhibit a relatively more negative response bias towards ambiguous stimuli (Daros, Costa, von Keyserlingk, Hötzel, & Weary, 2014).…”
Section: Emotionsmentioning
confidence: 92%
“…After separation, however, this approach response dropped to 62%, even though they continued to perform well with true white or red stimuli. The results suggested that, much like humans, when cows are distressed, they exhibit a relatively more negative response bias towards ambiguous stimuli (Daros, Costa, von Keyserlingk, Hötzel, & Weary, 2014).…”
Section: Emotionsmentioning
confidence: 92%
“…They found that when a tone was played with a frequency close to or equal to 4 kHz, rats housed in unstable conditions were slower to press the lever than rats housed in stable conditions, which is consistent with a decreased anticipation of reward. This "pessimistic" judgment bias has since been demonstrated in a few other species (including humans) and situations (Brilot et al, 2010;Daros et al, 2014;Hales et al, 2014;Mendl et al, 2009;Neave et al, 2013;Papciak et al, 2013;Scheele et al, 2013;Verbeek et al, 2014). Conversely, Swan and Hickman (2014) …”
Section: Resultsmentioning
confidence: 94%
“…Infectious diseases are often considered as the principal cause of calf mortality, specially gastro-intestinal disorders (Svensson and Liberg, 2006;Torsein et al, 2011;Bähler et al, 2012;Daros et al, 2014) and respiratory problems (Gulliksen et al, 2009). Moreover, farms with high calf mortality are regarded as of having poor welfare at the farm level (Ortiz-Pelaez et al, 2008;Kelly, 2013).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%